Las manos como símbolo, huella física del trabajo y proyecto ético en “Manos de obrero”, de Gabriela Mistral - Cuvardic García, Dorde (2014)
The human body is a recurring theme in Gabriela Mistral’s poetry. In “Manos de obrero”, from her poetry collection Lagar, the Chilean poet carries out a Marxist panegyric of the worker’s labor by focusing on the hands, a classic synecdoche of this social class. In addition, what stands out in Mistral’s poem is the detailed physical description of these hands marked by physical work. The hand here is inscribed with the effects of the exploitation of labor. Finally, the hand carries out an ethical, humanitarian function when, through the fruits of its labors, it provides daily necessities for its subjects, such as protection and affection. This article also relates these three modes of representation of the hand (iconographic, corporal/material and ethical) within the framework of Occidental labor discourse as well as the representation of the body in Mistral’s poetry.